Considerable variations in growth hormone policy and prescription in paediatric end-stage renal disease across European countries-a report from the ESPN/ERA-EDTA registry - van Huis, M; Bonthuis, M; Sahpazova, E; Mencarelli, F; Spasojević, B; Reusz, G; Caldas-Afonso, A; Bjerre, A; Baiko, S; Vondrak, K; Molchanova, E A; Kolvek, G; et al. (Nephrology, dialysis, transplantation, 2016)
BACKGROUND: Growth retardation in paediatric end-stage renal disease (ESRD) has a serious impact on adult life. It is potentially treatable with recombinant growth hormone (rGH). In this study, we aimed to quantify the variation in rGH policies and actual provided care in these patients across Europe. METHODS: Renal registry representatives of 38 European countries received a structured questionnaire on rGH policy. Cross-sectional data on height and actual use of rGH on children with ESRD aged <18 years were retrieved from the ESPN/ERA-EDTA Registry. RESULTS: In 21 (75%) of 28 responding countries, rGH is reimbursed for children with ESRD. The specific conditions for reimbursement (minimum age, maximum age and chronic kidney disease stage) vary considerably. Mean height standard deviation scores (SDS) at renal replacement therapy (RRT) [95% confidence interval (CI)] were significantly higher in countries where rGH was reimbursed -1.80 (-2.06; -1.53) compared with countries in which it was not reimbursed [-2.34 (-2.49;-2.18), P < 0.001]. Comparison of the mean height SDS at onset of RRT and final height SDS yielded similar results. Among the 13 countries for which both data on actual rGH use between 2007 and 2011 and data from the questionnaire were available, 30.1% of dialysis and 42.3% of transplanted patients had a short stature, while only 24.1 and 7.6% of those short children used rGH, respectively. CONCLUSION: Reimbursement of rGH associates with a less compromised final stature of ESRD children. In many countries with full rGH reimbursement, the actual rGH prescription in growth-retarded ESRD children is low and obviously more determined by the doctor's and patients' attitude towards rGH therapy than by financial hurdles.
Keywords: lidé; mladiství; Adult; registrace; Infant; Female; Kidney Failure, Chronic; dítě; Evropa; průzkumy a dotazníky; Prescription Drugs; tělesná výška; lékařská praxe - způsoby provádění; Adolescent; Humans; Infant, Newborn; průřezové studie; Cross-Sectional Studies; lidský růstový hormon; Registries; předškolní dítě; Practice Patterns, Physicians'; Child, Preschool; Renal Replacement Therapy; mužské pohlaví; mladý dospělý; novorozenec; ženské pohlaví; Young Adult; léky na předpis; Male; Human Growth Hormone; Europe; Body Height; Child; dospělí; Surveys and Questionnaires; náhrada funkce ledvin; kojenec; chronické selhání ledvin